Agalsidase alfa for the treatment of fabry disease: a closer look. (June 2014) - Lipinski, Shawn E; Komlodi-Pasztor, Edina; Goker-Alpan, Ozlem
Enzyme replacement therapies substitute particular enzymes in individuals who have deficient or absent levels of enzymatic activity due to inherited defects. Fabry disease, a rare X-linked genetic disorder yet common lysosomal storage disease, is due to the impaired activity of α-galactosidase A. Currently, there are two enzyme preparations available for the treatment of Fabry disease: agalsidase alfa (Replagal ® ), manufactured by Shire, and agalsidase beta (Fabrazyme ® ), manufactured by Genzyme. Here, we review the molecular characteristics and intracellular trafficking of the endogenous and exogenous enzymes as well as the pharmacological properties of Replagal. We also summarize clinical experiences with Replagal and provide insight into its therapeutic value for the treatment of Fabry disease.